Sejarah Peninggalan Benteng Pertahanan Jepang Di Desa Sumlili Di Kecamatan Kupang Barat Pada Masa Perang Dunia II Tahun 1942 - Modena, Maria; Taneo, Malkisedek; Wisnuwardana, I Gede W (FLORESIENSIS, 2024)
This study aims to 1) determine the history of Japanese defense forts, 2) determine the functions of Japanese defense forts, and 3) determine the current structure of Japanese defense forts. The location of this study is in Sumlili Village, West Kupang District. The technique for determining informants was carried out using snowball sampling. The data sources in this study were primary and secondary data sources. The data collection techniques used were interviews, observation, and document study. The results of this study are as follows: (1) The Japanese entered Sumlili Village in 1942, using warships and landing at Batulesa. (2) The Japanese fort in Sumlili Village was built during World War II and was used by the Japanese army to store weapons, as a place of rest, and for defense during the war. (3) Two Japanese forts remain today, located in different places but with the same structure.